Studi Yuridis Sosiologis Perlindungan Hukum Pencatatan Perkawinan Penghayat Kepercayaan Suku Samin di Kabupaten Blora - Fuadi, Mohammad Irvan Nafis; Zuhriah, Erfaniah; Muhammad, Muhammad (ARBITER: Jurnal Ilmiah Magister Hukum, 2025)
This study is motivated by the persistent gap between the constitutional recognition of indigenous belief adherents following Constitutional Court Decision No. 97/PUU-XIV/2016 and the actual administrative practices in Blora Regency, particularly regarding the marriage registration of the Samin community. This research aims to analyze the forms of legal protection, policy implementation, and the structural, substantive, and cultural barriers affecting the marriage registration of Samin Indigenous Faith Adherents. Using a qualitative approach and Lawrence M. Friedman’s legal system theory, data were collected through interviews, observations, and documentation, and analyzed using descriptive qualitative techniques. The findings reveal that although legal instruments such as Constitutional Court Decision No. 97/PUU-XIV/2016 and Government Regulation No. 40/2019 formally acknowledge indigenous believers, implementation at the local level remains constrained by administrative unpreparedness, limited public outreach, bureaucratic complexity, and low legal awareness. The practice of listing Islam on identity cards (KTP) has become a pragmatic strategy for administrative convenience, but it hinders the community’s ability to register marriages as indigenous belief adherents. The imbalance among legal structure, legal substance, and legal culture results in ineffective legal protection. This study concludes that systemic reforms are required, including capacity-building for local officials, the establishment of standardized procedures for marriage registration, the development of supportive local regulations, and more inclusive legal education and outreach programs. These recommendations are expected to ensure equal and culturally respectful marriage registration services for the Samin community.